THE KIND OF MINDFULNESS INTERVENTION FOR ANXIETY IN UNDERGRADUATE NURSING STUDENTS: A LITERATURE REVIEW - Rikhan Luhur Prasetya; Meidiana Dwidiyanti; Nur Setiawati Dewi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Undergraduate nursing students have experience high levels of anxiety caused by academic, clinical practice and final assignments. This anxiety results in a decrease in students’ intellectual abilities and the risk of experiencing academic failures. Mindfulness is an effective intervention for reducing anxiety. Objectives: This scoping review aims to determine the kind of mindfulness interventions to reduce anxiety in undergraduate nursing students. Design: This study used a scoping review through a review of articles the kind of mindfulness interventions to reduce anxiety in undergraduate nursing students. Data Sources: Search for articles accessed through a database, including: Science Direct, Scopus, Semantic Scholar, ProQuest and SpringerLink with a range of search years 2017 to 2021. The search for articles uses the boolean method of the “OR/AND” operator. The keywords used in the article search were “Mindfulness” AND “Anxiety” AND “Undergraduate”, AND “Nursing” OR “Mindfulness Based Cognitive Therapy” OR “Mindfulness Based Stress Reduction” OR “Mindfulness Based”. Review Methods: This article uses Arksey and O'Melley's model in the analysis. Identification and analysis using Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Scooping Review (PRISMA-SR). Results: The result of this literature review show contains 5 quantitative articles. This article summarizes the kind of mindfulness interventions used to reduce anxiety in nursing students are mindfulness based cognitive therapy, mindfulness meditation, virtual community mindfulness, mindfulness through smartphones, and spiritual mindfulness. Mindfulness intervention provides serenity, focus on the situation with full awareness, acceptance, improvement in physical health, psychological, empathy, and well-being. The mindfulness was carried out 6 times in a series of interventions. The stages of mindfulness interventions vary widely, but the point is to focus attention and acceptance with awareness. Conclusion: The kind of mindfulness interventions used to reduce anxiety in nursing students including: mindfulness based cognitive therapy, mindfulness meditation, virtual community mindfulness, mindfulness spiritual Islam and acceptance, and spiritual mindfulness.